A retrospective review of isolated gliptin-exposure cases reported to a state poison control system*. (March 2014) - Darracq, M. A.; Toy, J. M.; Chen, T.; Mo, C.; Cantrell, F. L.
Abstract Background. The dipeptidyl peptidase-4 (DPP-4) inhibitors sitagliptin, saxagliptin, and linagliptin are approved by the US Food and Drug Administration in the treatment of type-2 diabetes. Given the limited published information regarding human overdoses to these medications, our goal was to characterize such exposures. Methods. A state poison system database was retrospectively reviewed for all single-agent exposures to sitagliptin, saxagliptin, and linagliptin from 2006 to 2012. Case notes were reviewed and an observational case series was constructed from the data collected including age, weight, gender, circumstances surrounding exposure, symptoms, and outcome. Patients with co-ingestants, confirmed non-exposure, unknown outcomes, or other coding errors were excluded. Results. A total of 197 cases were identified: 135 cases were excluded (123 cases were excluded due to co-ingestants and 12 cases were lost to follow-up); 62 were included for review. No patients experienced hypoglycemia. One of 19 exposed pediatric (0–9 years of age) patients experienced symptoms and was safely managed at home after one episode of emesis. No symptom was experienced following unintentional ingestion by three adolescent (10–18 years of age) patients. Forty single-agent adult exposures to gliptins were included. Thirty-seven involved non-self-harm exposures resulting from double or triple doses; all were safely managed at home without reported symptoms. The majority of these ingestions involved sitagliptin. Three self-harm-adult exposures to gliptins were included for review. All the three were evaluated in a healthcare facility. One patient experienced abdominal discomfort after ingesting 700 mg of sitagliptin and was ultimately discharged from the emergency department. The other two patients experienced no reported symptoms. Conclusion. The majority of gliptin-exposed adult and pediatric/adolescent patients were safely managed at home and when evaluated in a healthcare facility, did not require hospitalization. Intentional self-harm-adult gliptin exposures were managed in a healthcare facility but rarely resulted in hospitalization or serious morbidity at doses up to 18 times the adult therapeutic dose. Additional studies are necessary to determine precise triage guidelines for the management of gliptin overdose.